Biological Properties of Vitamins of the B-Complex, Part 1: Vitamins B1, B2, B3, and B5 - Hrubša, Marcel; Siatka, Tomáš; Nejmanová, Iveta; Vopršalová, Marie; Kujovská Krčmová, Lenka; Matoušová, Kateřina; Javorská, Lenka; Macáková, Kateřina; Mercolini, Laura; Remião, Fernando; Máťuš, Marek; Mladěnka, Přemysl; et al. (Nutrients, 2022)
This review summarizes the current knowledge on essential vitamins B1, B2, B3, and B5. These B-complex vitamins must be taken from diet, with the exception of vitamin B3, that can also be synthetized from amino acid tryptophan. All of these vitamins are water soluble, which determines their main properties, namely: they are partly lost when food is washed or boiled since they migrate to the water; the requirement of membrane transporters for their permeation into the cells; and their safety since any excess is rapidly eliminated via the kidney. The therapeutic use of B-complex vitamins is mostly limited to hypovitaminoses or similar conditions, but, as they are generally very safe, they have also been examined in other pathological conditions. Nicotinic acid, a form of vitamin B3, is the only exception because it is a known hypolipidemic agent in gram doses. The article also sums up: (i) the current methods for detection of the vitamins of the B-complex in biological fluids; (ii) the food and other sources of these vitamins including the effect of common processing and storage methods on their content; and (iii) their physiological function.
Keywords: Avitaminosis; vitamin B komplex; vitamin K; avitaminóza; pantothenic acid; Thiamine; thiamin; Vitamin A; Vitamin K; thiamine; lidé; Humans; Vitamin B Complex; niacin; riboflavin; essential; vitamin A